1994
DOI: 10.1007/bf03258467
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of the Macrolide Antibiotics Erythromycin, Clarithromycin and Azithromycin on Terfenadine Steady-State Pharmacokinetics and Electrocardiographic Parameters

Abstract: SummaryTerfenadine is a nonsedating histamine HI-antagonist that, when given with ketoconazole, results in accumulation of parent terfenadine and altered cardiac repolarisation in susceptible individuals. This prospective cohort study, designed to assess macrolide effects on terfenadine pharmacokinetics and electrocardiogram (ECG) parameters, evaluated 18 healthy male and female volunteers who received terfenadine to steady-state. Equal numbers (6) were randomised to receive either erythromycin, clarithromycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…For example, terfenadine's plasma levels, which are usually below the assay detection limit of 5 ng/ml, were measurable in some but not all subjects pretreated with erythromycin (113,191), and the interaction with ketoconazole resulted in 16-to 73-fold reduction in the antihistamines' oral clearance (192). Pronounced variability was also found in the interaction of grapefruit juice with various CYP3A substrates (119).…”
Section: Interindividual Variabilitymentioning
confidence: 92%
“…For example, terfenadine's plasma levels, which are usually below the assay detection limit of 5 ng/ml, were measurable in some but not all subjects pretreated with erythromycin (113,191), and the interaction with ketoconazole resulted in 16-to 73-fold reduction in the antihistamines' oral clearance (192). Pronounced variability was also found in the interaction of grapefruit juice with various CYP3A substrates (119).…”
Section: Interindividual Variabilitymentioning
confidence: 92%
“…Honig et al reported that after oral administration of a regular dose of macrolides to healthy volunteers, EM evoked 15 ms of Q-T interval prolongation on average, while CAM and AZM did not elicit obvious Q-T interval prolongation (13). Other studies reported the maximum effect of CAM for corrected Q-T interval prolongation in healthy volunteers as being 7 to 11 ms (4,28).…”
Section: Vol 44 2000 Q-t Interval Prolongation By Macrolides 2633mentioning
confidence: 99%
“…Like ketoconazole, erythromycin has been reported to cause severe cardiac toxicity with terfenadine when coadministered in humans (Food and Drug Administration, 1990). Honig et al (1994) have reported that the plasma concentrations of terfenadine, which is undetectable when given alone (60 mg b.i.d. for 7 days), increased to detectable levels following coadministration of erythromycin (500 mg t.i.d.…”
mentioning
confidence: 99%